The System of Concepts As a Metalanguage of Forensic Science - V. O. Kuznetsov (Теория и практика судебной экспертизы)
Concepts are an integral part of a forensic activity forming a specific terminological system, determining forensic science’s metalanguage, distinguishing it from the related legal sciences: criminalistics and procedural law. The article aims to review the conceptual system of forensic science. The authors point out the heterogeneity of its terminological and conceptual systems, which results from the synthetic nature of this science. Based on the existing classifications of concepts and terms of the general theory of forensic science, a new classification is proposed, including not only traditionally recognized terms such as general and specific scientific, legal notions and special concepts of forensic expertology language, but also the so-called expert concepts: interdisciplinary, intermediate notions, obtained as a result of the transformation of basic sciences’s data. Interdisciplinary notions form the theoretical and conceptual framework for some kinds of forensic examinations, first of all, complex forensic psychological and psychiatric and forensic psychological examinations, which traditionally refer to them as ‘’expert’’. When used in quotation marks, the word ‘’expert’’ indicates the terms’ conditional character, indicating the scope of application and functioning of the concepts, contrasting them to the legal concepts of the same name and basic sciences’ categories.